Recognition, Diagnosis, and Treatment of Clostridioides difficile Enterocolitis Presenting Without Diarrhea: A Literature Review - Ezgi Yılmaz; Duygu Işıl Gencer; Mustafa Salih Akın; Meyha Şahin; Bahadır Ceylan; Ali Mert (Pathogens)
Diarrhea, as the well-known clinical feature of Clostridioides difficile infection (CDI), may be absent at the initial presentation, leading to delays in diagnosis. The delay is due to both underrecognition of such presentations and the dependence of CDI diagnosis on stool samples. This review was conducted to evaluate the literature for CDI cases presenting without diarrhea, raise awareness about the possibility of CDI in the differential diagnosis regardless of diarrhea, and assemble relevant data to harmonize clinical approaches. The PubMED Medline database was used to conduct this literature review, focusing on reported CDI cases presenting without diarrhea. After exclusions, 22 articles were included for analysis, providing data for 48 cases. This paper will present the selected clinical data of these 48 patients and follow a real-life case with a clinical course of CDI including presentation, diagnosis, management, and outcomes. The excessive mortality and bowel resection rates of CDI patients presenting without diarrhea were the notable findings. Poor prognosis was possibly inflated by delayed diagnoses in an unfamiliar setting, emphasizing the importance of a high index of suspicion to allow early recognition of CDIs in the appropriate clinical context despite the absence of diarrhea.